Tawhid and its implications for Islamic architecture - Spahic, Omer (Kulliyyah of Architecture and Environmental Design, IIUM, 2012)
This paper discusses the Islamic notion of tawhid (the Oneness of Allah) and its implications for Islamic architecture. The paper is divided into two major parts. Firstly, the meaning and significance of tawhid, as a cornerstone of the Islamic belief system, is presented. Secondly, tawhid’s most important implications for perceiving, creating and using Islamic architecture are explained. The paper seeks to enhance the awareness, both of the professionals and general readership, as to the centrality of the role of the concept of tawhid in correctly conceptualizing and practicing Islamic architecture. The nature of the paper, along with its content, methodology and conclusions, is conceptual and philosophical, rather than empirical. The paper concludes that Islamic architecture is an architecture that embodies the message of Islam. It both facilitates Muslims’ realization of the Islamic purpose and its divine principles on earth, and promotes a lifestyle generated by such a philosophy and principles. The implications of tawhid for Islamic architecture are ideological, rather than technical. Such is the profundity of the influence the concept of tawhid exerts on Islamic architecture – and on Islamic culture and civilization, in general – that it gives the latter its conspicuous soul and identity. Without the effect of tawhid, no architecture deserves to be dubbed ‘Islamic’.